STRATEGI PENGEMBANGAN LAYANAN ADMINISTRASI KEMAHASISWAAN - Elizah, Tenti; Hamengkubuwono, Hamengkubuwono; Harahap, Emmi Kholilah (Tarbiyatuna Kajian Pendidikan Islam, 2024)
This research aimed to explore the strategies for developing student administrative services at IAIN Curup and the contributing factors to these services' development. This case study involved administrative staff, students, and institutional leaders at IAIN Curup, recruited using purposive sampling methods. Data collection was conducted through interviews and observations and analyzed using an interactive model. Key findings of the research emphasized crucial indicators for enhancing student administrative services. Response time was prioritized by implementing flexible staff scheduling, enhancing information systems, and conducting periodic evaluations. Improvements in information accessibility were achieved through data standardization and optimization of digital access. Queue reduction was addressed through process engineering, staff augmentation, and effective dissemination of queue information. Quality of service was enhanced by satisfaction surveys, feedback analysis, and benchmarking practices. Integration of information systems involved comprehensive evaluations, data protection measures, and system maintenance. Enhancements in communication quality were realized through channel reviews, ensuring transparency, advancing technology, and providing staff training. Supporting the development of these services were institutional management support, investments in information technology, human resource training, interdepartmental cooperation, student involvement in improvements, and a commitment to continuous enhancement. Future research should extend these findings to different higher education contexts to validate the results.